Big Data Management Prototype Development for Analysis Various of Data - Sulistyo Heripracoyo (IAES Indonesia Section, 2015)
The phenomenon of big data is currently agrowing topic in the world of information technology. From someof the literature mentioned that manage big data can createsignificant value for the world economy, improving productivityand competitiveness of enterprises and the public sector as wellas creating a large economic surplus for consumers. However,from some of the information obtained, big data is still not widelyapplied in the company or organization. This study aimed toexplore more information about the big data and proceed withmaking an application prototype big data management. Toexperiment with big data storage that is database, this researchuse NoSQL database technology that can map the needs of bothstructured and unstructured. And this research will be carriedout migration of Relational Database (RDBMS) into the databaseMongoDB. Prototype will be create with the object of study isstructured and unstructured data. The expected result of thisresearch is a model or prototype of big data management thatcan help organizations and companies (especially education) tomake decisions based on various types of data.